Respuestas
Respuesta dada por:
0
Sea p(x)=3x^5-x^3+ax+b
como x= 0 es raiz entonces p(0) = 0
Reemplazando:
3(0)^5-(0)^3+a(0)+b = 0
0+b=0
Luego b=0
como x= 2 es raiz entonces p(2) = 0
Reemplazando:
3(2)^5-(2)^3+a(2)+b = 0
96-8+2a+0=0
2a=-88
a=-44
Respuesta a= -44 , b=0
como x= 0 es raiz entonces p(0) = 0
Reemplazando:
3(0)^5-(0)^3+a(0)+b = 0
0+b=0
Luego b=0
como x= 2 es raiz entonces p(2) = 0
Reemplazando:
3(2)^5-(2)^3+a(2)+b = 0
96-8+2a+0=0
2a=-88
a=-44
Respuesta a= -44 , b=0
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años